Oil Reserves in the Middle East: A Comprehensive Analysis - Haikal Gazi (International Journal of Science and Society, 2023)
The Middle East has long been recognized as a global hub for oil production, with substantial reserves that play a pivotal role in the world's energy supply. This scientific journal article provides a comprehensive analysis of oil reserves in the Middle East, offering insights into their geological formation, distribution, and the geopolitical implications associated with their exploitation. The article also explores the region's potential for sustainable resource management and the challenges it faces in an evolving global energy landscape.